Improvement of the Water Resistance of a Narrow‐Band Red‐Emitting SrLiAl3N4:Eu2+ Phosphor Synthesized under High Isostatic Pressure through Coating with an Organosilica Layer. (4th July 2016) - Tsai, Yi‐Ting; Nguyen, Hoang‐Duy; Lazarowska, Agata; Mahlik, Sebastian; Grinberg, Marek; Liu, Ru‐Shi
Abstract: A SrLiAl3 N4 :Eu 2+ (SLA) red phosphor prepared through a high‐pressure solid‐state reaction was coated with an organosilica layer with a thickness of 400–600 nm to improve its water resistance. The observed 4f 6 5d→4f 7 transition bands are thought to result from the existence of Eu 2+ at two different Sr 2+ sites. Luminescence spectra at 10 K revealed two zero‐phonon lines at 15377 (for Eu(Sr1)) and 15780 cm −1 (for Eu(Sr2)). The phosphor exhibited stable red emission under high pressure up to 312 kbar. The configurational coordinate diagram gave a theoretical explanation for the Eu 2+/3+ result. The coated samples showed excellent moisture resistance while retaining an external quantum efficiency (EQE) of 70 % of their initial EQE after aging for 5 days under harsh conditions. White‐light‐emitting diodes of the SLA red phosphor and a commercial Y3 Al5 O12 :Ce 3+ yellow phosphor on a blue InGaN chip showed high color rendition (CRI=89, R 9=69) and a low correlated color temperature of 2406 K.